P5 Proyek Bukan Produk - Hafriani, Masri, Sarah fazila (Bansigom Na Publisher, 2024)
The P5 Program, or Pancasila student profile Strengthening Project, and the PPRA program, or Rahmatan Lil Alamin student profile, are new innovations in the education curriculum that aim to improve the character and abilities of students as a whole. P5 centers on six dimensions: faith, global diversity, mutual aid, self-reliance, critical thinking, and creativity. Instead, the PPRA emphasizes moderate religious principles such as justice, tolerance, civility, and citizenship. Both of these programs aim to cultivate students ' personalities as Indonesian citizens and people around the world. The method of implementation of these two programs involves international PKM activities with the theme